2018
DOI: 10.1016/j.bbamem.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

RanGTPase regulates the interaction between the inner nuclear membrane proteins, Samp1 and Emerin

Abstract: Samp1, spindle associated membrane protein 1, is a type II integral membrane protein localized in the inner nuclear membrane. Recent studies have shown that the inner nuclear membrane protein, Emerin and the small monomeric GTPase, Ran are direct binding partners of Samp1. Here we addressed the question whether Ran could regulate the interaction between Samp1 and Emerin in the inner nuclear membrane. To investigate the interaction between Samp1 and Emerin in live cells, we performed FRAP experiments in cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Emerin has at least two modes of self-association with the potential to form networks or filaments (Berk et al, 2014; Herrada et al, 2015; Samson et al, 2017). Other partners include nucleo/cytoskeletal proteins (e.g., F-actin, myosin 1c, tubulin), nuclear membrane proteins (e.g., LAP1, Samp1) and transcriptional regulators such as HDAC3, b-catenin and Lmo7 (Holaska et al, 2006; Berk et al, 2013b; Shin et al, 2013; Barton et al, 2015; Vijayaraghavan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Emerin has at least two modes of self-association with the potential to form networks or filaments (Berk et al, 2014; Herrada et al, 2015; Samson et al, 2017). Other partners include nucleo/cytoskeletal proteins (e.g., F-actin, myosin 1c, tubulin), nuclear membrane proteins (e.g., LAP1, Samp1) and transcriptional regulators such as HDAC3, b-catenin and Lmo7 (Holaska et al, 2006; Berk et al, 2013b; Shin et al, 2013; Barton et al, 2015; Vijayaraghavan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Samp1 directs localization of gamma-tubulin, which is a major component of centrosomal complexes [ 22 ]. Furthermore, Samp1 interacts with LINC proteins SUN2, SUN1, emerin, and A-type lamins [ 23 , 24 , 25 ] and interferes with nuclear movement [ 26 ]. Samp1 is required for muscle cell differentiation, which was demonstrated in mouse myoblasts and human induced pluripotent stem cells [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerin interacts with many proteins during interphase [34,35], among which LUMA [41], HDAC3 [42], Btf [43], GCL [44], actin [45], Lmo7 [46], NET25 [47], and β-catenin [48] appear most crucial in the context of the structure of the cell nucleus, nuclear lamina, and chromatin. Emerin interacts with Samp1 (NET5) [92] and is indirectly involved in positioning of two chromosomes in the cell nucleus [93], but previous studies have also found no changes in location of chromosome territories in emerin-null patients [94].…”
Section: Discussionmentioning
confidence: 99%